O uso da intuição na construção de cenários em projetos de design estratégico - Ferronato, Priscilla Boff (Universidade do Vale do Rio dos Sinos, 2016)
The present research aims to connect the design project to a process of knowledge building. During the design project, when designers face situations that they do not have control of, they use their tacit knowledge. The design, by its strategic dimension, is able to read the signals of its own environment, interpret it and translate into future scenarios. Future scenarios in a metadesign perspective are the centre of the processuality of strategic design. The metadesign, as a knowledge platform, enables the designer to reflect critically on the project itself, in a non-linear and timeless process. Thus, the research tries to better understand the use of intuition in scenario building activities. Consequently, being able to move toward the understanding of design process. From the theoretical study, the definition of intuition is based on Bergson’s studies, the reconciliation with the immediate. Scenario building, therefore, is perceived as a space for the construction of narratives, where different views are shared. In order to meet the research objectives, the data were coded and analyzed by linkographics. The conclusion of this paper shows that the use of the intuition in scenario building activities relates to the ability of the designers to transform their procedures in immediate and experimental, emerging through associative and holistic connections. In the decision-making processes, in situations characterized by uncertainty, where the participants did not have enough specific knowledge, it was possible to see the predominance of the use of intuition. On the other hand, in the design moves characterized as ideation process, intuition can be related to a new construction process, able to drive and to increase the quality of the project. Intuition, therefore, is perceived as a project resource, a source of information against the unknown; however, it is intrinsic to the individual and its analysis should come from him.
Keywords: Intuição; Construção de cenários; Processo de projeto; Design estratégico; Intuition; Scenarios building; Design process; Strategic design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial